A Poetic History of the Oceans Literature and Maritime Modernity - Frank, Søren (Brill, 2022)
What is the ocean's role in human and planetary history? How have writers, sailors, painters, scientists, historians, and philosophers from across time and space poetically envisioned the oceans and depicted human entanglements with the sea? In order to answer these questions, Søren Frank covers an impressive range of material in A Poetic History of the Oceans: Greek, Roman and Biblical texts, an Icelandic Saga, Shakespearean drama, Jens Munk's logbook, 19th century-writers such as James Fenimore Cooper, Herman Melville, Jules Michelet, Victor Hugo, Jules Verne, Jonas Lie, and Joseph Conrad as well as their 20th and 21st century-heirs like J. G. Ballard, Jens Bjørneboe, and Siri Ranva Hjelm Jacobsen. A Poetic History of the Oceans promotes what Frank labels an amphibian comparative literature and mobilises recent theoretical concepts and methodological developments in Blue Humanities, Blue Ecology, and New Materialism to shed new light on well-known texts and introduce readers to important, but lesser-known Scandinavian literary engagements with the sea.